The Effect of China's Weak Institutional Environment on the Quality of Big 4 Audits - Ke, Bin; Lennox, Clive S.; Xin, Qingquan (The Accounting Review, 2015)
ABSTRACT This study examines whether China's weak institutional environment results in lower-quality audits by the Big 4 firms. We find that the Big 4 assign their less experienced partners to companies that are listed only in China compared with clients cross-listed in Hong Kong. The Big 4 are less likely to issue modified audit reports, and they charge lower audit fees for clients that are listed only in China. Finally, companies listed only in China have larger signed abnormal accruals than do companies cross-listed in Hong Kong. Overall, we conclude that the weak institutional environment in China results in the Big 4 firms providing lower-quality audits to companies that are listed only in China.